Safety and efficacy of laparoscopic radical gastrectomy after neoadjuvant chemotherapy plus immunotherapy: a retrospective cohort study - Xiong, Junjie; Zou, Yu; Zhang, Yunlong; He, Fan; Tang, Chenglin; Zhong, Kemei; Qian, Kun (Frontiers in Immunology, 2025)
BackgroundGastric cancer (GC) is a highly prevalent type of malignant tumor worldwide. Patients with locally advanced gastric cancer (LAGC) frequently have a poor prognosis due to the inability to achieve R0 resection. Neoadjuvant chemotherapy (NAC) can enhance survival rates, although its effectiveness is limited. Immune checkpoint inhibitors (ICIs) have demonstrated potential in treating advanced gastric cancer, but their efficacy in neoadjuvant therapy (NAT) for LAGC remains unclear. The aim of this study was to evaluate the safety, pathological response and survival outcome of neoadjuvant chemotherapy plus immunotherapy (NACI) versus NAC alone after laparoscopic gastrectomy for GC.MethodsA retrospective analysis of 375 patients with LAGC who received neoadjuvant therapy from 2015 to 2022 was performed. Patients were divided into NACI group (168 patients) and NAC group (207 patients) according to NAT regimen.ResultsThe rate of pathologic complete response (pCR, 20.2% vs. 12.6%, P=0.04) and the rate of major pathological response (MPR, 31.0% vs. 18.8%, P=0.007) in the NACI group are significantly higher than those in the NAC group, and the NACI group also had a higher rate of R0 resection (91.3% vs. 84.1%, P=0.028). The NACI group experienced a more significant decline in ypT0 (22.0% vs. 13.0%, P=0.022) and ypN0 (67.3% vs. 53.6%, P=007), but there was no difference in disease-free survival (DFS) and overall survival (OS) at 3 years between the two groups (P>0.05).ConclusionsNACI significantly improved pCR rates and R0 resection rates in patients with LAGC without increasing perioperative risk, but did not translate into short-term survival benefits.